Implementasi Sistem Keuangan Desa (SISKEUDES) dalam Pengelolaan Keuangan di Desa Kayuputih, Kecamatan Banjar, Kabupaten Buleleng - Yulia Dewi, Kadek Elma; Prabawati, Ni Putu Anik; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2020)
ABSTRACT The Village Finance System Application (Siskeudes) is an application developed one of them in the framework of village financial management in order to assist the village government in financial management and to realize a more responsible village government. The application of this program used since 2017 in Kayuputih Village is certainlly inseparable from problems. This study uses descriptive qualitative methods with observation, interviews, and documentationn. Theresults of the study are based on an analysis with three implementation indicators according to Charles O. Jones consisting of organization, interpretationaand applicationn which shows that the application of the Siskeudes has been implemented quite well as evidenced by the implementation of the Siskeudes to date andthe existence of the Siskeudes helping the village apparatus in the financial management process from planning to accountability. Keywords: Implementation, Sistem Keuangan Desa (Siskeudes), Kayuputih Village, Village Financial Management